A construção do saber geográfico no helenismo: II - As physiografias e a desmitificação de Gaia. - Antonio Carlos Vitte; Márcio Henrique de Mello Pereira (Confins)
The article discusses the demystification of Gaia in Greek culture that led to the emergence of Greek science with Aristotle, the base of Hellenic science with Theophrastus and Strabo. From the Ionians to Heraclitus and the atomists to Hippocrates, the Greek reason sought to understand and explain the origin of man and the earth no longer through myths, but in search of evidence in the very dynamics of nature, by highlighting at each historical moment the elements of nature that best synthesize the natural origin, as well as the metaphysical and ontological unity of the world.